Respuesta :

Answer:

1 hour 12 minutes x 3 = 3   hour(s) + 36 minute(s)

Step-by-step explanation:

Given:

1 hour 12 minutes x 3 = .-----------hours  -------------minute(s)

Solution:

1 Hour =  60 minutes

So you  First add 60 to 12 minutes

i.e 72 minutes

Now 3 times 72 minutes = 3 × 72 = 216 minutes

60 minutes = 1 hour

216 minutes = 60 + 60 + 60 +  36

                   =  1 hour + 1 hour + 1 hour + 36 minutes

                   = 3 hour(s) + 36 minute(s)

1 hour 12 minutes x 3 = 3   hour(s) + 36 minute(s)